The Factors that Influence Student Satisfaction During Online Learning on the Subject of Culinary in the Bachelor of Applied Culinary Program of UNY - Auliana, Rizqie; Rahmawati, Fitri; Mahanani, Thyara; Marwanti, Marwanti (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to determine: (1) the factors that influence student satisfaction during online learning on the subject of culinary in the Bachelor of Applied Culinary Program of UNY, (2) the factors that dominate student satisfaction during online learning on the subject of culinary in the Bachelor of Applied Culinary Program of UNY, (3) the factors of student dissatisfaction during online learning on the subject of culinary in the Bachelor of Applied Culinary Program of UNY. The type of research is quantitative with a survey method. The research was carried out in March-August 2022 with the subject being students of Bachelor of Applied Culinary Programs at UNY Wates & Gunung Kidul Campus. Total population 189 people. The sampling technique used was the purposive sampling method. The data collection technique used a questionnaire and the data analysis technique used was descriptive quantitative. The results of the study show that: (1) the factors that influence student satisfaction during online learning are good e-teaching, good e-resources, assessment, learning content, perceived flexibility, perceived usefulness, learner-learner interactions, learner-instructor interactions, self-regulated learning; (2) The most dominant factor influencing student satisfaction during online learning is assessment; (3) the factors that became a source of student dissatisfaction during online learning were not found. The research implications show that online learning or also called distance learning can be applied to vocational study programs. In the future, if special circumstances occur, online learning can be developed into fun learning.